2016
DOI: 10.1002/ijc.30408
|View full text |Cite
|
Sign up to set email alerts
|

HER2 loss in HER2‐positive gastric or gastroesophageal cancer after trastuzumab therapy: Implication for further clinical research

Abstract: Mechanisms of acquired resistance to trastuzumab-based treatment in gastric cancer are largely unknown. In this study, we analyzed 22 pairs of tumor samples taken at baseline and post-progression in patients receiving chemotherapy and trastuzumab for advanced HER2-positive [immunohistochemistry (IHC) 3+ or 2+ with in-situ hybridization (ISH) amplification] gastric or gastroesophageal cancers. Strict clinical criteria for defining acquired trastuzumab resistance were adopted. Loss of HER2 positivity and loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 26 publications
9
73
1
Order By: Relevance
“…De Silva et al[34] confirmed in vitro that MET is likely to be a significant mechanism of lapatinib resistance in vivo . Finally, we recently showed that HER2 loss may be associated with acquired resistance to first-line trastuzumab-based treatment in patients with initially HER2-positive GC[35]. All these evidences enhance the complex cross-talk between HER2 and its downstream pathway and stress the importance of further elucidating the strategies to overcome resistance to HER2-targeted therapy.…”
Section: Gc With Chromosomal Instabilitymentioning
confidence: 99%
“…De Silva et al[34] confirmed in vitro that MET is likely to be a significant mechanism of lapatinib resistance in vivo . Finally, we recently showed that HER2 loss may be associated with acquired resistance to first-line trastuzumab-based treatment in patients with initially HER2-positive GC[35]. All these evidences enhance the complex cross-talk between HER2 and its downstream pathway and stress the importance of further elucidating the strategies to overcome resistance to HER2-targeted therapy.…”
Section: Gc With Chromosomal Instabilitymentioning
confidence: 99%
“…This agent has had remarkable benefit in pretreated breast cancer patients, yet in the gastroesophageal cancer population, no demonstrable benefit was noted and the experimental arm was numerically slightly inferior. HER2 expression can change at the time of disease progression in approximately 1/3 of patients who have previously received trastuzumab-based therapy 84,85 . Similar results were seen in the second-line trial of MM-111 plus trastuzumab-based chemotherapy, where a lower rate of HER2 amplification was seen in pre-treatment biopsies than in archived tumor specimens 86 .…”
Section: Outstanding Questions: Resistance Treatment Opportunitiementioning
confidence: 99%
“…Second, IHC is semi-quantitative and notoriously subjective, while FISH is time-consuming and relatively expensive. Third, HER2 status might change during trastuzumab therapy[4], and neither IHC nor FISH are effective assays for reflecting the real-time scenario of HER2 status[5]. More convenient and reproducible detection methods are therefore needed to identify HER2-positive gastric cancer, thus facilitating the appropriate and effective use of HER2-targeted therapy[6].…”
Section: Introductionmentioning
confidence: 99%